2020
DOI: 10.48550/arxiv.2006.15018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The clustering dynamics of primordial black boles in $N$-body simulations

Manuel Trashorras,
Juan García-Bellido,
Savvas Nesseris

Abstract: We explore the possibility that Dark Matter (DM) may be explained by a non-uniform background of approximately stellar-mass clusters of Primordial Black Holes (PBHs), by simulating the evolution them from recombination to the present with over 5000 realisations using a Newtonian N -body code. We compute the cluster rate of evaporation, and extract the binary and merged sub-populations along with their parent and merger tree histories, lifetimes and formation rates; the dynamical and orbital parameter profiles,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Building on prior results [29,[33][34][35] (cf. also to [36]), we have argued in [32] that PBHs form clusters at very high redshifts which evaporate later due to the continuous loss of PBHs in the high energy tail of the Maxwell-Boltzman energy distribution. We have found that clusters of N cl ≈ 1300 with approximate densities n cl ≈ 3.6/pc 3 having formed at redshifts z ≈ 85 are evaporating at the current epoch.…”
mentioning
confidence: 83%
“…Building on prior results [29,[33][34][35] (cf. also to [36]), we have argued in [32] that PBHs form clusters at very high redshifts which evaporate later due to the continuous loss of PBHs in the high energy tail of the Maxwell-Boltzman energy distribution. We have found that clusters of N cl ≈ 1300 with approximate densities n cl ≈ 3.6/pc 3 having formed at redshifts z ≈ 85 are evaporating at the current epoch.…”
mentioning
confidence: 83%
“…Some of the uncertainty in the precise formation mechanism is bracketed by the cases S = 1 and the full expressions of Equations ( 9) and (10). More precise numerical simulations of PBH binary formation and evolution will be required for a more quantitative investigation of the sensitivity of our results to the formation model [15,[52][53][54][55].…”
Section: A Pbh Merger Modelsmentioning
confidence: 99%
“…However, despite the fact that the result for this PBH fraction matches the estimation of the merger rate by the LIGO collaboration (Abbott et al 2016c) and by other groups (Ali-Haïmoud 2018; Raidal et al 2019), such an extrapolation might not be well suited for the estimation of the merger rates for PBH fractions fP BH > 0.001 and it merely represents a qualitative result here. As we discussed in Section 3.3, the formation of large gravitationally-bound structures (such as DM halos) might prevent merger events from occurring altogether, while on the other hand, a choice of a more realistic model (for example, the one with the proper account of GR effects in dense clusters, as discussed in a recent paper by Trashorras et al (2020)) may complicate things even further.…”
Section: Pbh Mergers and Fpmentioning
confidence: 99%
“…A reliable estimate of the GW signatures from PBH binary mergers requires a good understanding of the process of formation of PBH binaries and their subsequent interactions with the surrounding matter that may disrupt the binaries (for example, see Raidal et al (2019) or Trashorras et al (2020)). Despite the fact that the bulk of this work is dedicated to PBH binaries, we also consider the effects of hyperbolic 2 close encounters (as suggested by Garc à a-Bellido & Nesseris (2017)), and how a proper account of these events could affect our final results.…”
Section: Introductionmentioning
confidence: 99%